The Pattern of Settlement Distribution in Disaster Prone Areas of Semarang City - Tsabit N, Chindy Dhia; Pigawati, Bitta (Jurnal Teknik Sipil dan Perencanaan, 2021)
The increase in population in Semarang City affects the trends in land use. Limited availability of land in contrast to the increasing demand for land has prompted residents to choose a place to live in a location not following its designation. Several settlements in Semarang City have developed in disaster-prone locations. This study aimed to determine the characteristics of settlements in disaster-prone areas, including aspects of land use, levels of vulnerability to natural hazards, and settlement distribution patterns. The research is a descriptive quantitative study with a spatial approach and utilizes images from remote sensing and Geographic Information systems (GIS). The results show that the settlements covering an area of 5,577 hectares or 33.5% of the total settlement area of Semarang City are in disaster-prone areas. Most disaster-prone areas have a moderate level of vulnerability. There are three patterns of settlement distribution in the study area, namely clustered, random, and dispersed patterns. Most districts in Semarang City have a random pattern of disaster-prone settlements. The settlement distribution pattern reflects the characteristics of each disaster-prone area.